Local Bifurcation and Persistence of an Ecological System Consisting of a Predator and Stage Structured Prey - Majeed, Azhar (Iraqi Journal of Science, 2023)
In this paper, the conditions of persistence of a mathematical model, consists froma predator interacting with stage structured prey are established. The occurrence oflocal bifurcation and Hopf bifurcation are investigated. Finally, in order to confirmour obtained analytical results, numerical simulations have been done for ahypothetical set of parameter values .